2018
DOI: 10.5115/acb.2018.51.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological changes in the common carotid artery of the male rat in induced hypogonadism

Abstract: The role of androgens in the development of cardiovascular diseases remains controversial. The current study therefore sought to determine the changes in the histomorphology of the common carotid artery of the male rat in orchidectomy-induced hypogonadism. Twenty-two Rattus norvegicus male rats aged 2 months were used. The rats were randomly assigned into baseline (n=4), experimental (n=9), and control (n=9) groups. Hypogonadism was surgically induced in the experimental group by bilateral orchiectomy under lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 67 publications
(92 reference statements)
2
3
0
Order By: Relevance
“…We reported a reduction of smooth muscle cell density of the tunica media of the LCAs in castrated adult male rabbits. Similar findings have been noted in the smooth muscle of the common carotid artery [21] and the penis [39] under settings of induced hypogonadism. Smooth muscle density increased to control levels in adult male castrated rabbits subsequently injected with testosterone, suggesting a reversible effect.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We reported a reduction of smooth muscle cell density of the tunica media of the LCAs in castrated adult male rabbits. Similar findings have been noted in the smooth muscle of the common carotid artery [21] and the penis [39] under settings of induced hypogonadism. Smooth muscle density increased to control levels in adult male castrated rabbits subsequently injected with testosterone, suggesting a reversible effect.…”
Section: Discussionsupporting
confidence: 87%
“…The present study demonstrates increased collagen fiber density in the tunica adventitia of the LCAs in hypo-androgenic rabbits. Other studies have reported similar changes in collagen fibers in the common carotid artery [21] and the penis [39] under induced androgen deficiency. We also found that vascular adventitial collagen fiber density remained elevated after administering testosterone to castrated rabbits.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations